Comprehensive Education in The Management of First - Year Students at VNU National Defense and Security Training Center - Tuan anh, Duong; Duan, Le Van (VNU Journal of Science: Education Research; Vol 39 No 1S, 2023)
Understanding the importance of comprehensive education, the direction of the National University of Hanoi until March 2023 is to develop a comprehensive education model for first-year students at the Vietnam National University, Hanoi - Hoa Lac. This initiative is being led by the Director of the Vietnam National University, Hanoi, Le Quan, will be implemented from the first semester of the academic year 2023-2024 with the goal of "being physically healthy, mentally strong, and socially skilled" [1]. VNU National Defense and Security Training Center is a member unit of the Vietnam National University, Hanoi with the function of providing national defense and security knowledge training. It is an ideal place for students to participate in learning activities that meet the objectives of the project. A research article on the effectiveness of comprehensive education in managing first-year students at the Center for National Defense and Security Education was conducted using methods such as soft skills training, organizing extracurricular activities, and improving physical and mental education for students. The statistical results show that after completing the National Defense and Security Education program, students observed significant changes in their soft skills such as communication, teamwork, and time management, as well as adopting a more scientific lifestyle and improving their physical fitness. Therefore, it can be seen that the application of comprehensive education in managing first-year students at the Vietnam National Defense and Security Training Center has been effective in improving the quality of extracurricular and sports activities and achieving positive results.